دور البنك الدولي في تعزيز الشمول المالي بالدول النامية-دراسة حالة الجزائرthe Role Of The World Bank In Promoting Financial Inclusion In Developing Countries - A Case Study Of Algeria (Journal of Economics and Management Research, 2023)
يهدف هذا البحث إلى ابراز الدور الذي تقوم به مجموعة البنك الدولي في تعزيز الشمول المالي بالدول النامية مع دراسة حالة الجزائر، وذلك بالاعتماد على تقرير المؤشر العالمي للشمول المالي لسنة 2017 الصادر عن البنك الدولي. وخلص هذا البحث إلى أن مجموعة البنك الدولي تساعد الدول النامية في تعزيز الشمول المالي من خلال تشكيلة من أدوات التمويل المختلفة مصحوبة بخدمات استشارية فنية. أما فيما يخص حالة الجزائر فقد سجلنا مستويات متوسطة للشمول المالي ولم نلمس جهود واضحة من مجموعة البنك الدولي لدعم وتعزيز الشمول المالي في الجزائر بسبب غياب إستراتيجية وطنية للشمول المالي. This research aims to highlight the role played by the World Bank Group in promoting financial inclusion in developing countries with the case study of Algeria, based on the report of the Global Inclusion Index for Financial Inclusion for the year 2017 issued by the World Bank. This research concluded that the World Bank Group assists developing countries in promoting financial inclusion through a variety of different financing instruments accompanied by technical advisory services. As for the case of Algeria, we recorded medium levels of financial inclusion and did not see clear efforts from the World Bank Group to support and enhance financial inclusion in Algeria due to the absence of a national strategy for financial inclusion.